An immobilized graphene oxide stationary phase for open-tubular capillary electrochromatography - Wang, Chun (2013)
The research literature currently abounds with studies of graphene-related materials as a result of the extraordinary properties of such materials. On the basis of these citations, it is clear that the range of applications for such materials is substantial. In this manuscript, we report the immobilization of graphene oxide (GO) onto a fused-silica capillary to form a potential stationary phase for use in open-tubular CEC. We successfully incorporated GO through an in situ condensation reaction with (3-aminopropyl)triethoxysilane after silanization with (3-aminopropyl)triethoxysilane on the inner surface of the capillary. This GO-incorporated capillary was then characterized by use of SEM, infrared spectroscopy, and measurements of EOF. The electrochromatographic features of this stationary phase have also been investigated. Evaluation of acquired data indicates high electrochromatographic resolution and good capillary efficiency. Highly reproducible results between runs, days, and capillaries were also obtained.